Open Data Policy and Privacy Challenges: Balancing Transparency and Security in Digital Governance in Indonesia - Nadia Lestari (Asian Digital Governance Problems, 2025)
Purpose: This study examines the evolving dynamics of Indonesia’s open data policy within the broader context of digital governance. It aims to understand how the state negotiates the balance between transparency and data protection, particularly after the implementation of the One Data Indonesia initiative and the enactment of the Personal Data Protection Law. The research explores how institutional culture, ethical reasoning, and governance structures shape the interpretation and practice of openness in a rapidly digitalizing public sector. Subjects and Methods: Using a qualitative, interpretive approach, the study analyzes policy documents, legal frameworks, and institutional reports, complemented by semi-structured interviews with policymakers, data officers, and civic actors. Data were interpreted through thematic and critical policy analysis to uncover the narratives, tensions, and ethical dilemmas surrounding open data implementation in Indonesia’s bureaucratic institutions. Results: The findings reveal that open data governance in Indonesia remains fragmented across ministries and local governments. Bureaucratic actors often view transparency as both an obligation and a risk, constrained by overlapping regulations and fear of data misuse. Ethical ambiguities persist as institutions struggle to harmonize openness with privacy protection amid growing concerns over cybersecurity and public trust. Conclusions: The study concludes that Indonesia’s open data reform represents a moral and institutional negotiation rather than a purely technical project. Sustainable transparency requires legal clarity, digital infrastructure, ethical literacy, and civic engagement to build a culture of trust that reconciles openness with security.